A Light‐Activated Acyl Carrier Protein "Trap" for Intermediate Capture in Type II Iterative Polyketide Biocatalysis. Issue 72 (6th December 2019) - Kilgour, Samantha L.; Kilgour, David P. A.; Prasongpholchai, Panward; O'Connor, Peter B.; Tosin, Manuela
Abstract: A discrete acyl carrier protein (ACP) bearing a photolabile nonhydrolysable carba(dethia) malonyl pantetheine cofactor was chemoenzymatically prepared and utilised for the trapping of biosynthetic polyketide intermediates following light activation. From the in vitro assembly of the polyketides SEK4 and SEK4b, by the type II actinorhodin "minimal" polyketide synthase (PKS), a range of putative ACP‐bound diketides, tetraketides, pentaketides and hexaketides were identified and characterised by FT‐ICR‐MS, providing direct insights on active site accessibility and substrate processing for this enzyme class. Abstract : A novel photoactivatable acyl carrier protein‐based tool provides novel insights on substrate iterative processing for a model type II iterative polyketide synthase.